Analisis Kebutuhan Media Digital Interaktif Berbasis Contextual Teaching and Learning: Pembelajaran Teks Cerita di Sekolah Dasar - Moh Zulfan Sauqi; Adhitya Yusron Fahmi; Adam Sidqi; Osama Ahmad; Rani Setiawaty (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the need for interactive digital media based on the Contextual Teaching and Learning (CTL) model in narrative text learning at the elementary school level. The research employed a qualitative approach using a case study design to obtain an in-depth understanding of students’ and teachers’ learning needs. Data were collected through interviews, questionnaires, and documentation involving fourth-grade teachers and students at SDN 3 Puyoh. The findings indicate that students show a strong preference for learning activities that involve observation, discussion, and reflection, with full agreement on the importance of contextual and interactive learning experiences. These activities align with the core principles of CTL, which emphasize active engagement, real-life connections, and collaborative learning. The integration of interactive digital media was found to enhance students’ understanding of narrative elements, increase learning motivation, and reduce learning boredom. This study concludes that interactive digital media based on CTL is not merely an alternative instructional tool, but a pedagogical necessity to support meaningful, relevant, and student-centered narrative text learning in elementary schools.